Recently developed electrospinning methods: a review - Hosseini Ravandi, Seyed Abdolkarim; Sadrjahani, Mehdi; Valipouri, Afsaneh; Dabirian, Farzad; Ko, Frank K (Textile research journal, 2022)
Conventional electrospinning is an effective and versatile method employed for fabricating nanofibers. However, the relatively low production rate is the major challenge of electrospinning as an economic and scalable method. Recently, several approaches have been developed to ensure the high production rate of nanofibers. This paper has reviewed the latest developed electrospinning methods, such as multi-jet, needleless, bubble, centrifuge and electro-centrifuge systems. Furthermore, the jet formation in centrifugal spinning, as well as electro-centrifuge systems, was investigated through experimental and numerical analysis.